Identifikasi Lapisan Akuifer Menggunakan Metode Geolistrik Resisitivitas Konfigurasi Dipole – Dipole Di Kelurahan Padang Mulya Kecamatan Koba - Daus, Reza Firdaus Fir; Widyaningrum, Yekti; Indriawati, Anisa (Jurusan Fisika, Universitas Bangka Belitung, 2023)
Padang Mulya Village, Koba District is part of the Koba Groundwater Basin area. This area has the potential of abundant aquifer layers. An aquifer is a layer of rock that can store water in large quantities. However, the continued increase in exploration of the aquifer layer will result in damage to the aquifer environment. In this case it is necessary to identify the aquifer layers to determine the depth and lithology of the constituent rocks. The resistivity geoelectric method of the dipole-dipole configuration is the most sensitive geophysical method for identifying aquifer layers. Measurements were made on six tracks to obtain data variations on current strength and potential difference. From these data variations in apparent resistivity values will be obtained. 2D modeling of the apparent resistivity value using the backward modeling method is carried out on each track in order to obtain a 2D cross-section of the subsurface structure. The 2D section of each track has an aquifer layer with a depth of 0 meters to 20 meters and is composed of clay, loamy sand, rather dense gravel sand and sandstone.